Dc power cable for photovoltaic power generation system and method for manufacturing the same
Patent Information
- Application Number
- CN202611276845.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]在光伏发电系统用交直流传输电力电缆的结构中,护套层材料作为重要组成部分,起到电力绝缘和防护的作用,其性能的好坏将会影响整个电力电缆的使用寿命和系统能否正常运作,行业内普遍采用聚烯烃作为护套层的主要原料,聚烯烃材料具有良好的绝缘性能、电气性能和机械强度,但其易燃性及燃烧时释放的有毒烟气易引发火灾和环境污染,传统卤系阻燃剂因释放有毒气体和腐蚀性物质逐渐受限,而无机阻燃剂常面临阻燃效率低、力学性能劣化等挑战,此外,聚烯烃分子结构对高温和紫外线敏感,长期暴露于高温或紫外线环境下易发生氧化降解,引发分子链断裂和交联,从而导致力学性能显著下降,且温暖潮湿的环境导致护套层材料易滋生细菌,腐蚀电力电缆芯材,从而严重限制了电力电缆的使用寿命
本发明利用2,2,6,6-四甲基哌啶胺与3-氯丙基三乙氧基硅烷发生亲核取代反应制备受阻胺基偶联剂,同时利用六氯环三磷腈为P、N源,三聚氰胺为N源,通过六氯环三磷腈和三聚氰胺的亲核取代反应制备聚磷腈密胺阻燃剂,然后在海泡石表面接枝受阻胺基偶联剂有助于海泡石在基体中的均匀分散,使聚磷腈密胺阻燃剂负载到海泡石表面,此外受阻胺官能团的引入可在一定程度上提升材料的紫外耐受性能,海泡石作为一种多孔结构,能够作为阻燃协效剂、抑烟剂和载体,具有降低烟量排放以及补强等作用,改性海泡石中负载的聚磷腈密胺阻燃剂构成磷-氮协同阻燃体系,通过改性海泡石的加入,能够显著提高材料的力学性能、紫外耐受性能、阻燃能力和抑烟能力。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of power cable technology, specifically relating to AC / DC transmission power cables for photovoltaic power generation systems and their manufacturing methods. Background Technology
[0002] Photovoltaic power generation systems utilize AC / DC transmission cables as the core carriers for achieving "photovoltaic conversion - power collection - grid connection and transmission," and their function is directly related to system safety and power generation efficiency. DC cables primarily connect photovoltaic modules, combiner boxes, and inverters, undertaking the task of collecting high-voltage, low-current photovoltaic power and ensuring stable transmission for over 25 years. AC cables connect the inverter to the distribution network, responsible for transmitting the AC power converted from DC to the grid or load end. They must match the inverter's output characteristics with grid connection standards to reduce transmission losses.
[0003] In the structure of AC / DC power transmission cables used in photovoltaic power generation systems, the sheath material is a crucial component, playing a vital role in electrical insulation and protection. Its performance directly impacts the lifespan of the entire power cable and the normal operation of the system. The industry commonly uses polyolefins as the main raw material for the sheath. Polyolefin materials possess excellent insulation, electrical properties, and mechanical strength; however, their flammability and the toxic fumes released during combustion can easily cause fires and environmental pollution. Traditional halogenated flame retardants are gradually being limited due to the release of toxic gases and corrosive substances, while inorganic flame retardants often face challenges such as low flame retardant efficiency and deterioration of mechanical properties. Furthermore, the molecular structure of polyolefins is sensitive to high temperatures and ultraviolet radiation; long-term exposure to high temperatures or ultraviolet radiation can easily lead to oxidative degradation, causing molecular chain breakage and cross-linking, resulting in a significant decrease in mechanical properties. Warm and humid environments also make the sheath material prone to bacterial growth, corroding the power cable core material and severely limiting the lifespan of the power cable. Summary of the Invention
[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide AC / DC power transmission cables for photovoltaic power generation systems and their preparation method. By introducing modified sepiolite and functional modifying additives, the sheath material of the power cable is endowed with good mechanical properties, UV aging resistance, antibacterial properties, flame retardancy, and high temperature resistance.
[0005] The objective of this invention can be achieved through the following technical solutions: A photovoltaic power generation system AC / DC transmission power cable includes, from the inside out, a conductor, a cross-linked polyethylene insulation layer, an inner sheath layer, an armor layer, and an outer sheath layer. Both the inner and outer sheath layers are prepared by drawing out a sheath layer material. The sheath layer material comprises the following components by weight: 70-90 parts low-density polyethylene, 10-15 parts ethylene-tetrafluoroethylene copolymer, 6-15 parts modified sepiolite, 3-7 parts functional modifying additives, 3-6 parts dicumyl peroxide, 2-5 parts triallyl isocyanurate, 1-3 parts plasticizer, and 0.1-1 parts lubricant. The modified sepiolite was prepared by grafting a hindered amine coupling agent, which was prepared by a nucleophilic substitution reaction between 2,2,6,6-tetramethylpiperidinamine and 3-chloropropyltriethoxysilane, onto the surface of sepiolite and loading it with a polyphosphazene melamine flame retardant; the polyphosphazene melamine flame retardant was prepared by a nucleophilic substitution reaction between hexachlorocyclotriphosphazene and melamine. The functional modified additive is prepared by ion crosslinking reaction of OCAP-POSS, phytic acid and modified chitosan; OCAP-POSS is synthesized by 3-aminopropyltriethoxysilane, concentrated hydrochloric acid and methanol; the modified chitosan is prepared by anion exchange reaction of (3-carboxypropyl)triphenylphosphonium bromide and silver tetrafluoroborate, with the modified quaternary phosphonium salt intermediate as a cationic monomer and the chitosan main chain as a thermally initiated synthesis.
[0006] Preferably, the preparation method of the modified sepiolite includes the following steps: I. Add 2,2,6,6-tetramethylpiperidinamine, anhydrous toluene and triethylamine to the reactor, heat to 110°C, stir and dissolve under nitrogen atmosphere, then slowly add 3-chloropropyltriethoxysilane, stir and react for 6-8 hours. After the reaction is completed, filter, wash and rotary evaporate to prepare the hindered amine coupling agent. II. Add hexachlorocyclotriphosphazene and dimethyl sulfoxide to the reactor and sonicate until fully dissolved. Then add melamine and place in a 90°C oil bath. Then slowly add triethylamine and stir at a constant temperature for 10 hours. After the reaction is completed, filter, wash and dry to prepare polyphosphazene melamine flame retardant. III. Add sepiolite and deionized water to the reactor, place it in a 70°C water bath and stir at 1200 r / min for 10 min to emulsify. Then add hindered amine coupling agent and stir for 5 min. Then add polyphosphazene melamine flame retardant and continue stirring for 2-4 h. After the reaction is completed, filter, wash and dry to prepare modified sepiolite.
[0007] Preferably, the mass ratio of hexachlorocyclotriphosphazene to melamine is 1:0.7~1.1.
[0008] Preferably, the mass ratio of sepiolite, hindered amine coupling agent and polyphosphazene melamine flame retardant is 5:1.2~2:4~7.
[0009] Preferably, the preparation method of the functional modified additive includes the following steps: (1) Dissolve (3-carboxypropyl)triphenylphosphonium bromide in dichloromethane, then slowly add a mixed solution of silver tetrafluoroborate and deionized water, stir at room temperature for 6-8 h, collect the lower organic phase after the reaction is complete, and prepare the modified quaternary phosphonium salt intermediate by vacuum distillation and thorough drying; (2) Chitosan was dissolved in 2 wt.% acetic acid solution and stirred thoroughly until completely dissolved. Then, modified quaternary phosphonium salt intermediate was added and complexing agent EDC·HCl was introduced. Initiator VA-044 was added under nitrogen atmosphere and kept for 15 min. Then, the reaction bottle was sealed and placed in an ultraviolet light initiation device with a main wavelength of 254 nm and a power of 24 W for 2 h. After the reaction was completed, it was purified and dried to prepare modified chitosan. (3) Add methanol, concentrated hydrochloric acid and 3-aminopropyltriethoxysilane to the reactor, stir and react at room temperature for 14 days, filter and separate, and wash thoroughly with cold methanol. Dry the obtained powder under vacuum at 60°C to prepare OCAP-POSS; (4) Take OCAP-POSS and deionized water and stir until completely dissolved to form a uniform solution. Take 70wt.% phytic acid solution and slowly add it to deionized water and stir continuously until the phytic acid is completely dispersed. Then mix it with the uniform solution, add ammonia water to adjust the pH value to 5, and stir continuously to mix evenly. Then add modified chitosan and stir to react for 3~4h. After the reaction is completed, filter, wash and dry to prepare the functional modified additive.
[0010] Preferably, the mass ratio of chitosan to modified quaternary phosphonium salt intermediate is 1:2~2.5.
[0011] Preferably, the mass ratio of OCAP-POSS, phytic acid solution and modified chitosan is 1:0.85~0.92:0.46~0.65.
[0012] Preferably, the preparation method of the sheath layer material includes the following steps: weighing each component according to the weight parts, adding low-density polyethylene, ethylene-tetrafluoroethylene copolymer, modified sepiolite, functional modified additives, plasticizer and lubricant into a mixer, mixing for 5-7 minutes, adding dicumyl peroxide and triallyl isocyanurate, mixing for 8-15 minutes to obtain a mixture, then using a flat vulcanizing machine to melt the obtained mixture at 120-125°C for 5-7 minutes, and then placing it at 170-180°C and 14-16 MPa for a crosslinking reaction for 25-30 minutes to prepare the sheath layer material.
[0013] Preferably, the plasticizer is one or more of dioctyl adipate, dimethyl phthalate, dioctyl phthalate, and diisodecyl phthalate; and the lubricant is one or more of stearic acid, polyethylene wax, and oxidized polyethylene wax.
[0014] The method for manufacturing AC / DC power transmission cables for photovoltaic power generation systems as described above includes the following steps: S1. A cross-linked polyethylene insulation layer is extruded onto the outside of the conductor using an extruder. The conductor is a type 5 soft conductor and is manufactured using a unidirectional stranding process. S2. An inner sheath layer is formed by extruding sheath material onto the outside of the cross-linked polyethylene insulation layer. S3. A steel strip is wrapped around the outside of the inner sheath to form an armor layer; S4. An outer sheath layer is formed by extruding sheath material on the outside of the armor layer to prepare an AC / DC power transmission cable for a photovoltaic power generation system.
[0015] The beneficial effects of this invention are: This invention utilizes a nucleophilic substitution reaction between 2,2,6,6-tetramethylpiperidinamine and 3-chloropropyltriethoxysilane to prepare a hindered amine coupling agent. Simultaneously, using hexachlorocyclotriphosphazene as the P and N source and melamine as the N source, a polyphosphazene melamine flame retardant is prepared through a nucleophilic substitution reaction between hexachlorocyclotriphosphazene and melamine. Grafting the hindered amine coupling agent onto the surface of sepiolite facilitates the uniform dispersion of sepiolite in the matrix, allowing the polyphosphazene melamine flame retardant to be loaded onto the sepiolite surface. Furthermore, the introduction of hindered amine functional groups can improve the material's UV resistance to a certain extent. Sepiolite, as a porous structure, can act as a flame retardant synergist, smoke suppressant, and carrier, reducing smoke emissions and providing reinforcement. The polyphosphazene melamine flame retardant loaded in the modified sepiolite constitutes a phosphorus-nitrogen synergistic flame retardant system. The addition of modified sepiolite significantly improves the material's mechanical properties, UV resistance, flame retardancy, and smoke suppression capabilities.
[0016] This invention utilizes anion exchange reaction between (3-carboxypropyl)triphenylphosphonium bromide and silver tetrafluoroborate to prepare a modified quaternary phosphonium salt intermediate with broad-spectrum antibacterial activity. Then, using the modified quaternary phosphonium salt intermediate as a cationic monomer and chitosan as the main chain, a modified chitosan with good bactericidal function is synthesized via thermal initiation. Simultaneously, octa(γ-chloroaminopropyl)polyhedral oligomeric silsesquioxane (OCAP-POSS) is synthesized using 3-aminopropyltriethoxysilane, concentrated hydrochloric acid, and methanol. Finally, using OCAP-POSS as a nanoscale organic-inorganic hybrid material, OCAP-POSS, phytic acid, and modified chitosan are crosslinked via an ionic crosslinking reaction to prepare a modified chitosan with good antibacterial function. The modified additives include OCAP-POSS, whose unique cage-like structure (Si-O-Si framework) can effectively improve the density of the carbon layer. Phytic acid, as a phosphorus-rich biomass, can serve as an acid source. The modified chitosan structure is also rich in carbon and nitrogen, which can serve as both a carbon and gas source, significantly enhancing the flame retardant properties of the material. In addition, the Si-O-Si framework introduced into the molecular structure of the functional modified additives helps to improve the thermal stability of the material and enhance its high-temperature resistance. At the same time, OCAP-POSS's own UV inertness and nano-effect can endow the modified material with excellent UV shielding properties, and it works synergistically with the modified sepiolite to exert a good resistance to UV aging. Detailed Implementation
[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0018] Example 1: A method for preparing modified sepiolite includes the following steps: I. Add 4.7g of 2,2,6,6-tetramethylpiperidinamine, 10mL of anhydrous toluene and 3.5g of triethylamine to the reactor, heat to 110℃, stir and dissolve under nitrogen atmosphere, then slowly add 7g of 3-chloropropyltriethoxysilane, stir and react for 8h. After the reaction is completed, filter, wash and rotary evaporate to prepare the hindered amine coupling agent. II. Add 2g of hexachlorocyclotriphosphazene and 150mL of dimethyl sulfoxide to the reactor and sonicate until fully dissolved. Then add 1.8g of melamine and place in a 90℃ oil bath. Then slowly add triethylamine and stir at a constant temperature for 10h. After the reaction is completed, filter, wash and dry to prepare polyphosphazene melamine flame retardant. III. Add 5g of sepiolite and 500mL of deionized water to the reactor, place it in a 70℃ water bath and stir at 1200r / min for 10min for emulsification treatment, then add 1.6g of hindered amine coupling agent and stir for 5min, then add 6.2g of polyphosphazene melamine flame retardant and continue stirring for 3h. After the reaction is completed, filter, wash and dry to prepare modified sepiolite.
[0019] Example 2: A method for preparing a functional modified additive includes the following steps: (1) Dissolve 10.7g of (3-carboxypropyl)triphenylphosphonium bromide in 120mL of dichloromethane, and then slowly add a mixed solution of 4.9g of silver tetrafluoroborate and 10mL of deionized water. Stir the reaction at room temperature for 7h. After the reaction is complete, collect the lower organic phase and distill it under reduced pressure and dry it thoroughly to prepare the modified quaternary phosphonium salt intermediate. (2) Take 2g of chitosan and dissolve it in 2wt.% acetic acid solution. Stir well until completely dissolved. Then add 4.4g of modified quaternary phosphonium salt intermediate and introduce 0.4‰ complexing agent EDC·HCl. Add 0.03g of initiator VA-044 under nitrogen atmosphere and keep for 15min. Then seal the reaction bottle and place it in a UV initiation device with a main wavelength of 254nm and a power of 24W for 2h. After the reaction is completed, purify it several times with anhydrous ethanol and dry it to prepare modified chitosan. (3) Add 200 mL of methanol, 27 mL of concentrated hydrochloric acid and 30 mL of 3-aminopropyltriethoxysilane to the reactor, stir and react at room temperature for 14 days, filter and separate, and wash thoroughly with cold methanol. Dry the obtained powder under vacuum at 60 °C to prepare OCAP-POSS; (4) Take 10g of OCAP-POSS and 100mL of deionized water and stir until completely dissolved to form a uniform solution. Take 8.8g of 70wt.% phytic acid solution and slowly add it to 50mL of deionized water and continue stirring until the phytic acid is completely dispersed. Then mix it with the uniform solution, add ammonia water to adjust the pH value to 5, and continue stirring to mix evenly. Then add 5.6g of modified chitosan and stir to react for 4h. After the reaction is completed, filter, wash and dry to prepare the functional modified additive.
[0020] Example 3 A sheath layer material comprises the following components in parts by weight: 74 parts of low-density polyethylene, 10.5 parts of ethylene-tetrafluoroethylene copolymer, 6.3 parts of modified sepiolite prepared in Example 1, 3.3 parts of functional modified additive prepared in Example 2, 3.2 parts of dicumyl peroxide, 2.2 parts of triallyl isocyanurate, 1.1 parts of plasticizer dimethyl phthalate, and 0.2 parts of lubricant oxidized polyethylene wax.
[0021] The preparation method of the above-mentioned sheath layer material includes the following steps: weigh each component according to the weight parts, add low-density polyethylene, ethylene-tetrafluoroethylene copolymer, modified sepiolite, functional modification additives, plasticizer and lubricant into a mixer, mix for 5 minutes, add dicumyl peroxide and triallyl isocyanurate, mix for 10 minutes to obtain a mixture, then use a flat vulcanizing machine to melt the obtained mixture at 120°C for 6 minutes, and then place it at 175°C and 15MPa for crosslinking reaction for 27 minutes to prepare the sheath layer material.
[0022] A method for manufacturing an AC / DC power transmission cable for a photovoltaic power generation system includes the following steps: S1. A cross-linked polyethylene insulation layer is extruded onto the outside of the conductor using an extruder. The conductor is a type 5 soft conductor and is stranded in the same direction. S2. An inner sheath layer is formed by extruding sheath material onto the outside of the cross-linked polyethylene insulation layer. S3. A steel strip is wrapped around the outside of the inner sheath to form an armor layer; S4. An outer sheath layer is formed by extruding sheath material on the outside of the armor layer to prepare an AC / DC power transmission cable for a photovoltaic power generation system.
[0023] Example 4 A sheath layer material comprises the following components in parts by weight: 81 parts of low-density polyethylene, 12.7 parts of ethylene-tetrafluoroethylene copolymer, 10.4 parts of modified sepiolite prepared in Example 1, 5.5 parts of functional modified additive prepared in Example 2, 4.2 parts of dicumyl peroxide, 3.6 parts of triallyl isocyanurate, 1.9 parts of plasticizer dimethyl phthalate, and 0.5 parts of lubricant oxidized polyethylene wax.
[0024] The preparation method of the above-mentioned sheath material and the preparation method of AC / DC transmission power cable for photovoltaic power generation system are the same as in Example 3.
[0025] Example 5 A sheath layer material comprises the following components in parts by weight: 88 parts of low-density polyethylene, 14.5 parts of ethylene-tetrafluoroethylene copolymer, 14.7 parts of modified sepiolite prepared in Example 1, 6.8 parts of functional modified additive prepared in Example 2, 5.7 parts of dicumyl peroxide, 4.8 parts of triallyl isocyanurate, 2.5 parts of plasticizer dimethyl phthalate, and 0.7 parts of lubricant oxidized polyethylene wax.
[0026] The preparation method of the above-mentioned sheath material and the preparation method of AC / DC transmission power cable for photovoltaic power generation system are the same as in Example 3.
[0027] Comparative Example 1: A method for preparing a functional modified additive includes the following steps: (1) Add 200 mL of methanol, 27 mL of concentrated hydrochloric acid and 30 mL of 3-aminopropyltriethoxysilane to the reactor, stir and react at room temperature for 14 days, filter and separate, and wash thoroughly with cold methanol. Dry the obtained powder under vacuum at 60 °C to prepare OCAP-POSS; (2) Take 10g of OCAP-POSS and 100mL of deionized water and stir until completely dissolved to form a homogeneous solution. Take 8.8g of 70wt.% phytic acid solution and slowly add it to 50mL of deionized water and continue stirring until the phytic acid is completely dispersed. Then mix it with the homogeneous solution, add ammonia water to adjust the pH value to 5, and continue stirring to mix evenly. Then add 5.6g of chitosan and stir to react for 4h. After the reaction is completed, filter, wash and dry to prepare the functional modified additive.
[0028] Comparative Example 2: A sheathing material comprises the following components in parts by weight: 88 parts of low-density polyethylene, 14.5 parts of ethylene-tetrafluoroethylene copolymer, 14.7 parts of sepiolite, 6.8 parts of functional modified additive prepared in Example 2, 5.7 parts of dicumyl peroxide, 4.8 parts of triallyl isocyanurate, 2.5 parts of plasticizer dimethyl phthalate, and 0.7 parts of lubricant oxidized polyethylene wax.
[0029] The preparation method of the above-mentioned sheath material and the preparation method of AC / DC transmission power cable for photovoltaic power generation system are the same as in Example 3.
[0030] Comparative Example 3: A sheathing material comprises the following components in parts by weight: 88 parts of low-density polyethylene, 14.5 parts of ethylene-tetrafluoroethylene copolymer, 14.7 parts of modified sepiolite prepared in Example 1, 6.8 parts of functional modified additive prepared in Comparative Example 1, 5.7 parts of dicumyl peroxide, 4.8 parts of triallyl isocyanurate, 2.5 parts of plasticizer dimethyl phthalate, and 0.7 parts of lubricant oxidized polyethylene wax.
[0031] The preparation method of the above-mentioned sheath material and the preparation method of AC / DC transmission power cable for photovoltaic power generation system are the same as in Example 3.
[0032] Comparative Example 4: A sheathing material comprises the following components in parts by weight: 88 parts of low-density polyethylene, 14.5 parts of ethylene-tetrafluoroethylene copolymer, 14.7 parts of modified sepiolite prepared in Example 1, 5.7 parts of dicumyl peroxide, 4.8 parts of triallyl isocyanurate, 2.5 parts of plasticizer dimethyl phthalate, and 0.7 parts of lubricant oxidized polyethylene wax.
[0033] The preparation method of the above-mentioned sheath material and the preparation method of AC / DC transmission power cable for photovoltaic power generation system are the same as in Example 3.
[0034] Performance testing The performance of the sheathing materials prepared in Examples 3-5 and Comparative Examples 2-4 was tested: (1) Mechanical properties and UV aging resistance test: The tensile properties were tested according to GB / T 1040.2-2022. After being irradiated for 72 hours at 60℃ with a 40W UV lamp (wavelength 290~400nm) (the sample was turned over for 36 hours in the middle to ensure uniform irradiation), the change rate of tensile strength and elongation at break was tested. The distance between the sample and the lamp tube was 254mm. The UV aging resistance of the sample was evaluated in this way. The data results are shown in Table 1.
[0035] (2) Antibacterial performance test: The antibacterial performance of the sample was evaluated by measuring the diameter of the inhibition zone using the agar diffusion method. The test strain was Staphylococcus aureus, and the data results are shown in Table 1.
[0036] (3) Limiting oxygen index test: The test was conducted in accordance with GB / T 2406.2-2009. The sample size was 100mm×6.5mm×3mm. The data results are shown in Table 1.
[0037] (4) Vertical burning test: The test was conducted according to the vertical burning test (UL-94). The sample size was 125mm×13mm×3.2mm. The data results are shown in Table 1.
[0038] (5) High temperature resistance test: The sample was placed in a TGA-103 thermogravimetric analyzer and heated from room temperature to 800℃ at a heating rate of 5℃ / min under nitrogen protection. The initial decomposition temperature of the material was recorded, and the high temperature resistance of the sample was evaluated. The data results are shown in Table 1.
[0039] Table 1 Sample performance test results
[0040] As can be seen from the data results in Table 1, the samples prepared in Examples 3-5 of this invention possess good mechanical properties, UV aging resistance, antibacterial properties, flame retardant properties, and high-temperature resistance. In Comparative Example 2, no sepiolite modification treatment was performed, and its measured tensile strength and elongation at break were lower than those in Examples 3-5. This is because the aggregation of nanoparticles led to a decrease in mechanical properties, and the measured changes in tensile strength and elongation at break were significantly different compared to Examples 3-5. The flame retardant properties were also lower than those in Examples 3-5, indicating that the grafting of hindered amine coupling agents and the loading of polyphosphazene melamine flame retardants are beneficial to improving the mechanical properties, UV aging resistance, and flame retardant properties of the samples. The functional modifying additives added in Comparative Example 3 did not modify chitosan, and no functional modifying additives were introduced in Comparative Example 4. The measured values of gold in Comparative Examples 3-4 were lower than those in Comparative Examples 4. The diameter of the inhibition zone of Staphylococcus aureus was lower than that in Examples 3-5, indicating that the grafting of the modified quaternary phosphonium salt intermediate is beneficial to improving the antibacterial properties of the sample. Moreover, the diameter of the inhibition zone of Staphylococcus aureus in Comparative Example 4 was significantly lower than that in Comparative Example 3, indicating that the modified quaternary phosphonium salt intermediate and chitosan grafting in the functional modification additive have a more superior antibacterial effect. In addition, the change rate of tensile strength and the change rate of elongation at break in Comparative Example 4 were significantly different from those in Examples 3-5, while the flame retardant properties and the initial thermal decomposition temperature were lower than those in Examples 3-5, indicating that the introduction of the functional modification additive is also beneficial to improving the UV aging resistance, flame retardant properties and high temperature resistance of the sample.
[0041] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0042] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. An AC / DC power transmission cable for a photovoltaic power generation system, characterized in that, The material comprises, from the inside out, a conductor, a cross-linked polyethylene insulation layer, an inner sheath layer, an armor layer, and an outer sheath layer. Both the inner and outer sheath layers are prepared by drawing out a sheath layer material. This sheath layer material comprises the following components by weight: 70-90 parts low-density polyethylene, 10-15 parts ethylene-tetrafluoroethylene copolymer, 6-15 parts modified sepiolite, 3-7 parts functional modifying additives, 3-6 parts dicumyl peroxide, 2-5 parts triallyl isocyanurate, 1-3 parts plasticizer, and 0.1-1 parts lubricant. The modified sepiolite was prepared by grafting a hindered amine coupling agent, which was prepared by a nucleophilic substitution reaction between 2,2,6,6-tetramethylpiperidinamine and 3-chloropropyltriethoxysilane, onto the surface of sepiolite and loading it with a polyphosphazene melamine flame retardant; the polyphosphazene melamine flame retardant was prepared by a nucleophilic substitution reaction between hexachlorocyclotriphosphazene and melamine. The functional modified additive is prepared by ion crosslinking reaction of OCAP-POSS, phytic acid and modified chitosan; OCAP-POSS is synthesized by 3-aminopropyltriethoxysilane, concentrated hydrochloric acid and methanol; the modified chitosan is prepared by anion exchange reaction of (3-carboxypropyl)triphenylphosphonium bromide and silver tetrafluoroborate, with the modified quaternary phosphonium salt intermediate as a cationic monomer and the chitosan main chain as a thermally initiated synthesis.
2. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 1, characterized in that, The preparation method of the modified sepiolite includes the following steps: I. Add 2,2,6,6-tetramethylpiperidinamine, anhydrous toluene and triethylamine to the reactor, heat to 110°C, stir and dissolve under nitrogen atmosphere, then slowly add 3-chloropropyltriethoxysilane, stir and react for 6-8 hours. After the reaction is completed, filter, wash and rotary evaporate to prepare the hindered amine coupling agent. II. Add hexachlorocyclotriphosphazene and dimethyl sulfoxide to the reactor and sonicate until fully dissolved. Then add melamine and place in a 90°C oil bath. Then slowly add triethylamine and stir at a constant temperature for 10 hours. After the reaction is completed, filter, wash and dry to prepare polyphosphazene melamine flame retardant. III. Add sepiolite and deionized water to the reactor, place it in a 70°C water bath and stir at 1200 r / min for 10 min to emulsify. Then add hindered amine coupling agent and stir for 5 min. Then add polyphosphazene melamine flame retardant and continue stirring for 2-4 h. After the reaction is completed, filter, wash and dry to prepare modified sepiolite.
3. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 2, characterized in that, The mass ratio of hexachlorocyclotriphosphazene to melamine is 1:0.7~1.
1.
4. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 2, characterized in that, The mass ratio of sepiolite, hindered amine coupling agent and polyphosphazene melamine flame retardant is 5:1.2~2:4~7.
5. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 1, characterized in that, The preparation method of the functional modified additive includes the following steps: (1) Dissolve (3-carboxypropyl)triphenylphosphonium bromide in dichloromethane, then slowly add a mixed solution of silver tetrafluoroborate and deionized water, stir at room temperature for 6-8 h, collect the lower organic phase after the reaction is complete, and prepare the modified quaternary phosphonium salt intermediate by vacuum distillation and thorough drying; (2) Chitosan was dissolved in 2 wt.% acetic acid solution and stirred thoroughly until completely dissolved. Then, modified quaternary phosphonium salt intermediate was added and complexing agent EDC·HCl was introduced. Initiator VA-044 was added under nitrogen atmosphere and kept for 15 min. Then, the reaction bottle was sealed and placed in an ultraviolet light initiation device with a main wavelength of 254 nm and a power of 24 W for 2 h. After the reaction was completed, it was purified and dried to prepare modified chitosan. (3) Add methanol, concentrated hydrochloric acid and 3-aminopropyltriethoxysilane to the reactor, stir and react at room temperature for 14 days, filter and separate, and wash thoroughly with cold methanol. Dry the obtained powder under vacuum at 60°C to prepare OCAP-POSS; (4) Take OCAP-POSS and deionized water and stir until completely dissolved to form a uniform solution. Take 70wt.% phytic acid solution and slowly add it to deionized water and stir continuously until the phytic acid is completely dispersed. Then mix it with the uniform solution, add ammonia water to adjust the pH value to 5, and stir continuously to mix evenly. Then add modified chitosan and stir to react for 3~4h. After the reaction is completed, filter, wash and dry to prepare the functional modified additive.
6. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 5, characterized in that, The mass ratio of chitosan to the modified quaternary phosphonium salt intermediate is 1:2~2.
5.
7. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 5, characterized in that, The mass ratio of OCAP-POSS, phytic acid solution and modified chitosan is 1:0.85~0.92:0.46~0.
65.
8. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 1, characterized in that, The preparation method of the sheath layer material includes the following steps: weigh each component according to the weight parts, add low-density polyethylene, ethylene-tetrafluoroethylene copolymer, modified sepiolite, functional modification additives, plasticizer and lubricant into a mixer, mix for 5-7 minutes, add dicumyl peroxide and triallyl isocyanurate, mix for 8-15 minutes to obtain a mixture, then use a flat vulcanizing machine to melt the obtained mixture at 120-125℃ for 5-7 minutes, and then place it at 170-180℃ and 14-16MPa for crosslinking reaction for 25-30 minutes to prepare the sheath layer material.
9. The AC / DC power transmission cable for a photovoltaic power generation system according to claim 1, characterized in that, The plasticizer is one or more of dioctyl adipate, dimethyl phthalate, and diisodecyl phthalate; the lubricant is one or more of stearic acid, polyethylene wax, and oxidized polyethylene wax.
10. A method for preparing an AC / DC power transmission cable for a photovoltaic power generation system according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1. A cross-linked polyethylene insulation layer is extruded onto the outside of the conductor using an extruder. The conductor is a type 5 soft conductor and is manufactured using a unidirectional stranding process. S2. An inner sheath layer is formed by extruding sheath material onto the outside of the cross-linked polyethylene insulation layer. S3. A steel strip is wrapped around the outside of the inner sheath to form an armor layer; S4. An outer sheath layer is formed by extruding sheath material on the outside of the armor layer to prepare an AC / DC power transmission cable for a photovoltaic power generation system.